Ecological-anatomical adaptations of Mentha longifolia under in situ and ex situ conditions - Aygun, S (Plant Science Today, 2026)
This study aims to determine the effects of environmental factors across different ecosystems on the anatomy of the medicinally important species Mentha longifolia L. and to reveal its adaptation mechanisms. Comparative analyses were performed using anatomical, microscopic, histochemical and biometric methods to clarify the extent and nature of anatomical variability in ecotypes of the species, thereby exploring their potential for environmental adaptation. Anatomical sections of the species were stained using histological reagents and permanent slides were prepared for subsequent analysis. This study represents the first comparative analysis of the ecological-anatomical characteristics of M. longifolia under in situ and ex situ conditions. Furthermore, statistical analysis of micrometric indicators confirmed the species’ climatic resilience and adaptive responses to stress. In the in situ ecotype, parenchymatic excretion, an active “punctate-porous” cellular structure in the rhizome and well-developed aerenchyma (in rhizome cortex - in situ: 51.51 ± 4.955 µm; ex situ: 43.29 ± 4.014 µm) were identified. In ex situ specimens, parenchyma cell size differences were statistically significant (e.g., in the leaf - in situ: 31.52 ± 2.279 µm; ex situ: 37.51 ± 2.465 µm). Additionally, variations were observed in the xylem lumen diameter (e.g., in the stem - in situ: 23.54 ± 1.664 µm; ex situ: 29.31 ± 2.252 µm). The structural adaptations revealed through comparative ecological-anatomical studies represent evolutionary advancements in plant anatomy and possess substantial scientific and practical relevance. This comprehensive research, systematically conducted for the first time on Azerbaijans’ flora, confirms the ecological plasticity of the species.